Assessment of body mass index and prevalence of obesity among undergraduate medical students: an observational study in a tertiary care teaching hospital of Madhya Pradesh - Guleri, Sunil K.; Panika, Ram K.; Mahore, Rakesh K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Obesity is the major cause of various non-communicable diseases including diabetes mellitus, hypertension. The modifiable factors like stress, sedentary life, consumption of soft drinks and fast foods and lack of physical activity are responsible for it. Objective: to find dietary pattern, physical activity and status of overweight and obesity among medical students. Methods: It was a cross sectional observational study conducted on MBBS undergraduates studying in a g medical college at Sagar district of Madhya Pradesh, India. Out of nearly 500 medical students studying in different semesters, 300 students were participated in the study though the required sample size was 184 only. Structured questionnaire for interview, calibrated portable weight scale for weight measurement and stadiometer for height measurement were used. Results: The students were categorised into underweight, normal and overweight/obese on the basis of their calculated BMI (body mass index) value as per norms of World health organization for south Asian populations. 26.7% medical students were found to be overweight or obese based on BMI cut off value 23.00 kg/m2. There was lack of inclusion of fresh fruits and green vegetables in regular diet in 50% and nearly 95% of medical students respectively. The low level of physical activity was found in more than 85% of the medical students. Conclusions: The involvement of medical students in physical and sports activities is dire need for their good health.